Analisis Pelayanan Baitul Maal Wat Tamwil Raudhatul Hasanah (BMT Raudhah) Melalui Perspektif Hifdzul Mal - Kembaren, Nurul Fadhilah Yusri; K, Kusmilawaty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find facts related to Baitul Maal Wat Tamwil Raudhatul Hasanah (BMT Raudhah) services. The research method used is field research and literature with a qualitative approach. The data source used in this research is primary data. The data source obtained in this data is through interviews with 3 customers as informants. The data collection method uses observation which involves direct observation of objects, events, individuals, or situations to collect relevant information or data. The research results obtained show that BMT Raudhah's services are in accordance with Hifdzul Maal's perspective. Where Baitul Maal Wat Tamwil Raudhatul Hasanah (BMT Raudhah) in providing services has maintained ethical, justice and moral values in business and finance in accordance with Islamic principles in accordance with the perspective of Hifdzul Maal. However, to improve several program areas, such as expanding awareness of Hifdzul Maal, development opportunities are still found so that future services can be improved and more optimal. Therefore, it can be suggested that service providers must strive to provide effective and quality services in all forms of communication and interaction with customers.